Median Nerve Injury After Removal of Subdermal Implantable Contraceptive - Christensen, Joani M. (Hand (N Y), 2017)
Background: Subdermal implantable contraceptives are highly effective, approved in over 60 countries, and used by millions of women. Due to simple insertion and removal protocols, these procedures are often performed in the outpatient clinic setting, and procedural complications are rare. However, given the location of the implant in the medial antebrachial interval, there is a risk of neurovascular injury, especially with malpositioned or deeply placed implants. Methods: We present a case of proximal median nerve injury leading to severe neuropathy after attempted removal of a subdermal implantable contraceptive requiring neurolysis and tendon transfers. Results: At 6 months post surgery, the patient regained flexion of the index interphalangeal joints and protective sensation in the thumb and index fingers. Conclusions: Subdermal implant retrieval can lead to nerve injury, despite the relative simplicity of the procedure. If difficulty is encountered, imaging or open retrieval should be considered. Improvement in function can be gained through operative interventions including neurolysis and tendon transfers in the setting of severe neuropathy.